ANALISIS BREAK EVENT POINT (BEP) PADA RUMAH INDUSTRI KERUPUK DEVI LAROS BANYUWANGI - Khatimah, Khusnul (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2024)
Break even point analysis as the basis for determining the right selling price policy to optimize profitability in the CV cracker industry. Devi Laros Banyuwangi. The purpose of this study is to determine and analyze the effect of selling prices based on break even points (break even point) on company profitability. The object used in this study is the CV. Devi Laros Banyuwangi. In this study the problem raised is the determination of the product selling price. Data obtained from this study analyzed its profitability optimization before using the break even point selling price method, then selling price and net profit planning the following year using a break even point analysis and analyzed profitability optimization. The data analysis method uses a quantitative method that is to calculate data with cost-volume-profit analysis to analyze the effect of break even points on company profitability. Based on the calculation results, it can be seen that in 2017 the calculation of the quantity of 28,080 balls with a selling price of Rp. 80,000 get a break even point of Rp. 545,078,058. The level of profit or profitability of the company during the period 2015 - 2017 tends to increase. The profitability of the company increases after setting its selling price using cost-volume-profit analysis. The old selling price of Rp. 80,000, while the new selling price of Rp. 82,000. The ratio of operating profit using the old price of 0.2777 while the ratio of operating profit using the new price of 0.2929 means an increase in the ratio of operating profit from the old price to the new price.